Reconstruction of Pilonidal Sinus by Rhomboid Flap : Our Experience (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Pilonidal sinus is a common disease of young adult usually caused by insertion of fallen hair into skin (Gluteal cleft). Wide excision surgery is a common practice but due to high recurrence and long duration of healing there are more simple alternatives. Our experience with transposition of Rhomboid flap in the treatment of pilonidal sinus are described. The conventional way of treatment of pilonidal sinus is block excision and lay open of the sinus result in 5-14 days hospital stay healing time of 6-10 weeks. In our study all patients hospital stay was 2-3 days, healing time was less than two weeks with minimum complication. The aim of the study is to do rhomboid flap for the treatment of pilonidal sinus, so to avoid complications and recurrence, to shorten hospital stay and to give better outcome.Methods: Total 6 patients of 18-40 years of age after doing all investigations and clinical examinations, excision of pilonidal sinus was done and repaired by rhomboid transposition flap in the same setting. All the patients were followed up post operatively for 3 months to see any discharging sinus.Results: All 6 patients were discharged on 3rd post operative day and stitches were removed on 8th post operative day and approximate time to resume their work is 14 days.Conclusion: Pilonidal sinus surgery is a challenging operation for the surgeon because of recurrence and complication. Rhomboid flap technique has become familial because of its advantage of early healing, less hospital stay and very low recurrence rate.Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 17-19